2020
DOI: 10.1371/journal.pntd.0008032
|View full text |Cite
|
Sign up to set email alerts
|

Zika and dengue but not chikungunya are associated with Guillain-Barré syndrome in Mexico: A case-control study

Abstract: Background Zika, dengue and chikungunya viruses (ZIKV, CHIKV and DENV) are temporally associated with neurological diseases, such as Guillain-Barré syndrome (GBS). Because these three arboviruses coexist in Mexico, the frequency and severity of GBS could theoretically increase. This study aims to determine the association between these arboviruses and GBS in a Mexican population and to establish the clinical characteristics of the patients, including the severity of the infection. A case-control study was cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
2
17
0
2
Order By: Relevance
“…The authors suggested that CHIK too is an important cause of GBS and coinfection with Zika might increase the severity of GBS. However, in a recent study of 97 patients from Mexico,[ 8 ] Zika (8) and Dengue (4) were found to have a stronger association with GBS than CHIK (1).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that CHIK too is an important cause of GBS and coinfection with Zika might increase the severity of GBS. However, in a recent study of 97 patients from Mexico,[ 8 ] Zika (8) and Dengue (4) were found to have a stronger association with GBS than CHIK (1).…”
Section: Discussionmentioning
confidence: 99%
“…While Zika virus (ZIKV) is only characterized by mild acute symptoms, recent outbreaks in French Polynesia (2013) and the American continent (2016) showed severe long-term neurological complications in infants and adults [60,61]. The most prominent neuropathological condition of congenital infection is microcephaly, whereas infection in adults may result in encephalitis, myelitis and Guillain-Barre syndrome (GBS) [62][63][64]. GBS is characterized as a sudden onset weakness of the limbs associated with loss of reflexes and ascending paralysis [114].…”
Section: (+) Ssrna Virusesmentioning
confidence: 99%
“…Peripheral nervous system (PNS) involvement in DENV infection occurs in 5% of neurological symptoms, and includes Guillain-Barré syndrome (GBS), which is not commonly observed; hypokalemic quadriparesis or plegia; mononeuritis multiplex; brachial plexitis; diaphragmatic paralysis; and myositis [ 80 , 92 , 93 , 94 , 95 , 96 ]. GBS is an immune-mediated disorder of the PNS that manifests as acute onset of ascending paralysis and sensory symptoms [ 97 ], and is the most common cause of acute flaccid paralysis globally [ 98 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%